Physically protected carbon stocks in a Brazilian Oxisol under homogeneous forest systems - Silva, Maicon dos Santos da; Barreto-Garcia, Patrícia Anjos Bittencourt; Monroe, Paulo Henrique Marques; Pereira, Marcos Gervasio; Pinto, Luiz Alberto da Silva Rodrigues; Nunes, Marcio Renato (Geoderma Regional, 2025)
The soil organic carbon (SOC) stock and its occlusion within aggregates is at the center of discussions regarding climate change and global warming, as it is one of the mechanisms capable of mitigating the effects of these phenomena. Despite this, studies on the topic in tropical soils under native forest species plantations are still scarce. Therefore, we developed this study asking how SOC and occluded carbon stocks in aggregates respond to homogeneous Pterogyne nitens (N-fixing species) and Eucalyptus urophylla plantations when compared to a native forest? The study was conducted in Oxisol under three forest systems: two homogeneous plantations (P. nitens and E. urophylla) and a native forest (NF), located in the State of Bahia, Brazil. Litter and soil samples were collected up to a meter deep. The soil samples were subjected to physical fractionation by wet sieving, obtaining three size classes of water-stable aggregates: macroaggegates (2000–250 μm), microaggregates (250–53 μm) silt+clay (< 53 μm). The macroaggegates and microaggegates were sonicated to separate free and occluded particulate carbon. The carbon in whole soil and occluded in the aggregates were determined by the wet acidified oxidation method. The SOC stock (depth 100 cm) showed a reduction in the P. nitens plantation (123.1 Mg ha−1) and maintenance in the E. urophylla plantation (194.4 Mg ha−1) when compared to the NF (240.9 Mg ha−1). Occluded carbon showed a lower value in plantations compared to NF, representing an average of 5.8 % of the SOC. The P. nitens plantation negatively impacted SOC stock as a result of lower litter amounts and higher litter decomposition rates. In contrast, the E. urophylla plantation maintained SOC stocks close to those found in the NF due to the large amounts of litter and its high recalcitrance. Both forest plantations affect carbon occlusion in the aggregates, and therefore the SOC is poorly protected physically. [Display omitted]